Autophosphorylation is required for high kinase activity and efficient transformation ability of proteins encoded by host range alleles of v-src. - Woods, K M (1994)
pp60v-src is a nonreceptor protein tyrosine kinase that can transform both chicken and rodent fibroblasts. The src homology 2 (SH2) domain of this protein serves a critical role in the regulation of protein tyrosine kinase activity. The host range proteins pp60v-src-L, which contains a deletion of a highly conserved residue (Phe-172) in the SH2 domain, and pp60v-src-PPP, which contains a change from a Leu to a Phe at amino acid 186 in the SH2 domain, transform chicken but not rat cells and have slightly reduced kinase activity measured in vitro. The data presented here show that these altered proteins require autophosphorylation on Tyr-416 for high kinase activity and transforming ability. In the absence of autophosphorylation, there is a further decrease of at least threefold in in vitro kinase activity relative to the phosphorylated host range parental protein, no morphological transformation, a reduction in anchorage independent growth, and no disruption of the actin cytoskeleton. In addition, these SH2 mutations abolish the ability of the SH2 domain to bind a phosphorylated peptide that corresponds to the autophosphorylation site of pp60src. Thus, like mutant alleles of c-src encoding transformation competent proteins, and unlike v-src, transformation by pp60v-src-F172 delta and pp60v-src-L186F is dependent on phosphorylation of Y-416 for high kinase activity and transformation ability. The dependence of transformation on phosphotyrosine is not a reflection of an intramolecular interaction between the autophosphorylation site and the SH2 domains since purified SH2 domains are incapable of binding phosphorylated autophosphorylation site peptides in vitro.